(untitled) (Research, Society and Development, 2023)
The purpose of this study was to conduct a literature review on the use of prebiotics and probiotics as a complement to the pharmacological treatment of colorectal cancer, aiming to promote the activity of beneficial bacteria in restoring the healthy function of the intestinal microbiota. The methodology employed in the research was a narrative literature review with the objective of finding studies, results, and evidence of the therapeutic potential in the use of prebiotics and probiotics in aiding and treating this cancer. The results we obtained showed that this usage benefits the intestinal microbiota by increasing the presence of beneficial bacteria, which assist in digestion and reduce intestinal polyps, leading to intestinal balance and proper functioning. It can be concluded that it was possible to observe that the use of probiotics and prebiotics has a beneficial effect on the prevention and treatment of colorectal cancer, as they contribute to the maintenance of the intestinal microbiota, suppressing mutagenic characteristics, thus preventing dysbiosis and the possible initiation of a carcinogenesis process.